Implementering av PICC-line - en kvalitativ studie av anestesisykepleieres erfaringer - Stine Thorvaldsen Smith; Kristin Haraldstad (Septentrio Academic Publishing, 2019)
PICC-line, a peripherally inserted central venous catheter has been implemented by several Norwegian hospitals in recent years. Nurse Anesthetists play an important role in this process, and have been given new tasks as a result of PICC-line implementation. This study aimed to describe Nurse Anesthetists' experiences with implementation of PICC-line in hospital. A qualitative design, the data are based on three focus groups interviews with fifteen nurse anesthetists. The interviews were analyzed using a hermeneutic approach. Being a PICC-line nurse led to a feeling of competence, independence, motivation and meaningfulness. The implementation required good structure and organization, as well as enthusiasm. Collaboration and support influenced the implementation process. Good organization and enough available personnel, as well as good collaboration and support from the Anesthesiologists and the management are essential for a successful implementation.